Improving Community Welfare of SMEs Through Learning Community - Nurhidayati NURHIDAYATI; Ken SUDARTI; Ardian ADHIATMA (Communications of International Proceedings, 2021)
Learning has a strategic role in creation, acquisition and development of organizational knowledge so as to encourage innovation behavior. The power of knowledge creation can be the key to achieving a sustainable competitive advantage in the face of change. This study aims to develop a model of SMEs’ welfare through learning inter-relation processes of SMEs in the entrepreneurial community. Increasing the welfare of SMEs can be improved through learning activities by seeking and sharing knowledge. Previous research has shown that collaborative learning in the community is the basis for creating new knowledge that can be used to improve the performance of SMEs through value creation.
Keywords: Entrepreneurship Learning Community; Community Knowledge Creation; Open Innovation; Value Creation; SMEs Community Welfare